Nursing care in the light of elderly patient safety (Research, Society and Development, 2021)
Introduction: Patient safety was classified as a nursing assignment by the World Health Organization with the aim of reducing unnecessary harm to health and providing efficacy during hospitalizations. Objective: To describe the importance of nursing care related to the safety of elderly patients. Methodology: This is an integrative review, where documents for the research were obtained and studies were chosen through data collection from publications by reference authors in the area, with subsequent critical reading of titles and abstracts, in the Virtual Health Library ( BVS), using the following Health Science Descriptors (DESC) for the search and selection of data: “Nurse”, “Patient safety” and “Elderly”, using the Boolean operator “AND” among them in the research. Results: A category was created to discuss the theme, entitled “The main safety measures used by nurses for elderly patients”. Final considerations: It is essential that clinical care for human beings includes a safe space, in which the client is informed about the therapy, restrictions, threats and necessary precautions during the treatment. In this circumstance, nursing as a knowledge and occupation that assists individuals and groups in a unique and multidimensional way needs that concepts, studies and practice are linked to promote reliable clinical treatment.